Project-based Sukuk issuance for sustainable toll road refinancing in Indonesia: A confirmatory factor analysis - Farikhi, Amrin; Utomo, Christiono; Ismal, Rifki (Edelweiss Applied Science and Technology, 2025)
This paper examines the factors determining the issuance of project-based Sukuk for sustainable refinancing of toll road development in Indonesia. A questionnaire survey was used to obtain the factors that determine the issuance of project-based Sukuk. Experts and practitioners were consulted to identify and analyze the factors influencing the issuance of project-based Sukuk. The questionnaire participants included experienced infrastructure practitioners, regulators, and researchers. The results show that twelve indicators explain the decision to issue project-based Sukuk. Among them, the exchange rate is the most significant influence, with a loading factor value of 0.935, indicating that exchange rates affect Sukuk issuance, followed by the high cost of funds with a value of 0.857, which suggests that the high cost of funding is a strong reason for companies to choose Sukuk as an alternative for infrastructure refinancing. Other indicators, such as the inflation rate with a value of 0.835 and firm competence with a value of 0.809, also have a significant influence. This paper provides valuable findings and references for a toll road project-based Sukuk refinancing scheme to take over a stalled toll road project. The revealed factors benefit toll road stakeholders, such as business entities and the government, when preparing a refinancing scheme.